The impact of radiofrequency exposure on Aedes aegypti (Diptera: Culicidae) development - Nik Abdull Halim, Nik Muhammad Hanif; Mohd Jamili, Alya Farzana; Dom, Nazri Che; Abd Rahman, Nurul Huda; Kareem, Zana Jamal; Dapari, Rahmat (Public Library of Science, 2024)
Introduction Wireless communication connects billions of people worldwide, relying on radiofrequency electromagnetic fields (RF-EMF). Generally, fifth-generation (5G) networks shift RF carriers to higher frequencies. Although radio, cell phones, and television have benefitted humans for decades, higher carrier frequencies can present potential health risks. Insects closely associated with humans (such as mosquitoes) can undergo increased RF absorption and dielectric heating. This process inadvertently impacts the insects’ behaviour, morphology, and physiology, which can influence their spread. Therefore, this study examined the impact of RF exposure on Ae. aegypti mosquitoes, which are prevalent in indoor environments with higher RF exposure risk. The morphologies of Ae. aegypti eggs and their developments into Ae. aegypti mosquitoes were investigated. Methods A total of 30 eggs were exposed to RF radiation at three frequencies: baseline, 900 MHz, and 18 GHz. Each frequency was tested in triplicate. Several parameters were assessed through daily observations in an insectarium, including hatching responses, development times, larval numbers, and pupation periods until the emergence of adult insects. Results This study revealed that the hatching rate for the 900 MHz group was the highest (79 ± 10.54%) compared to other exposures (p = 0.87). The adult emergence rate for the 900 MHz group was also the lowest at 33 ± 2.77%. A significant difference between the groups was demonstrated in the statistical analysis (p = 0.03). Conclusion This work highlighted the morphology sensitivity of Ae. aegypti eggs and their developments in the aquatic phase to RF radiation, potentially altering their life cycle.